Pyostomatitis vegetans in a pediatric patient with ulcerative colitis: case report of a rare pediatric inflammatory bowel disease extraintestinal manifestation and review of the literature. Issue 7 (July 2020) - Bardasi, Giulia; Romagnoli, Andrea; Foschini, Maria P.; Mantovani, Alessio; Alvisi, Patrizia
Abstract : Inflammatory bowel diseases can occur with a wide range of extraintestinal symptoms, among which pyostomatitis vegetans, that is a rare but almost pathognomonic finding. We report the case of a 9-year-old female patient affected by ulcerative colitis and recently treated for an oral candidiasis, who experienced a relapse in her ulcerative colitis (PUCAI 50), preceded by the return of whitish lesions in the oral cavity, initially misdiagnosed and unsuccessfully treated as candidiasis and then recognized as pyostomatitis vegetans. Bloody diarrhea was treated with oral beclomethasone, with rapid remission of ulcerative colitis and disappearance of pyostomatitis vegetans. After 2 years, ulcerative colitis is in sustained remission with oral mesalamine and pyostomatitis vegetans has not recurred. Pyostomatitis vegetans is considered a marker of ulcerative colitis relapse among adult population, and although very few pediatric cases are described, it is very important to remember it in the differential diagnosis of the oral manifestations and comorbidities of inflammatory bowel diseases.